Analisis Kesalahan Berbahasa dalam Menulis Teks Pidato Bahasa Arab Siswi Kelas 5 Pondok Modern Arrisalah Ponorogo - Patmalia, Nia (Mahira: Journal of Arabic Studies, 2021)
This study aims to describe and explore: 1) Forms of language errors, 2) Factors causing language errors, 3) Efforts that can be made to minimize language errors in writing Arabic speech texts for grade 5 students. This study uses a qualitative content analysis approach. on language errors in 3 samples of Arabic speech texts for 5th grade Arrisalah Islamic Boarding School students in the 2019 Academic Year. The results showed language errors at the phonological level, morphological level, syntactic level, and semantic level. Factors that cause language errors that affect these errors are: mother tongue interference, inability to obey Arabic rules, compulsion to use Arabic, and ignoring penalties for language violators. Solutions to minimize errors are: nahwu and sharaf learning innovation, referring to Arabic mu'jam, adding insight into Arabic and improving language skills, being serious in writing speech texts, motivating students to be enthusiastic in using Arabic holding ishlah al-lughah and activities with Arabic themes, as well as increasing discipline in the use of language.